The heat, the heart and beyond: a narrative review of the many ways climate change impacts human health - Ouambo Talla, Achille Wilfred; Ascierto, Alessia; Sanvido, Anna; Severi, Paolo; Trabuio, Alessandro; Ceccolini, Francesca; Fortini, Francesca; Vieceli Dalla Sega, Francesco; Levenson, Anait S.; Vaccarezza, Mauro; Pasti, Luisa; Rizzo, Paola (Frontiers in Climate, 2025)
This article provides a narrative review of recent literature on the health impacts of climate change, synthesizing epidemiological findings, mechanistic insights, and policy implications across major exposure domains. Anthropogenic climate change is fundamentally altering global climate systems, with significant and multifaceted implications for human health. Epidemiological data indicate a strong correlation between ambient temperature fluctuations and cardiovascular mortality. Moreover, the frequency and severity of wildfires have intensified due to climate change, contributing to elevated levels of fine particulate matter (PM2.5) and resulting in substantial premature mortality. Climate change is modifying the geographic distribution and seasonality of vector-borne and zoonotic diseases, posing new challenges for infectious disease control. Air quality degradation alongside heightened UV radiation, contributes to a higher incidence of respiratory diseases, skin cancers, and ocular disorders. Climate-induced disruptions to agricultural systems are undermining food security, leading to increased malnutrition and related morbidity. Additionally, the psychological burden of climate-related events, including natural disasters and displacement, has been linked to rising rates of anxiety, post-traumatic stress disorder (PTSD), and affective disorders. These effects are more evident in vulnerable populations, including the elderly, individuals with pre-existing health conditions, those of lower socioeconomic status, and populations residing in low-income countries. Urgent mitigation strategies targeting greenhouse gas emissions are required to limit further climate-related health burdens. Concurrently, adaptive strategies must be implemented to bolster resilience across ecological, infrastructural, and health systems. Although public health systems are critical in addressing these challenges, a coordinated, multidisciplinary research agenda is imperative to elucidate the complex pathways linking climate change and health, and to develop evidence-based interventions aimed to reduce its negative impacts on human health.